Determining Moodle Self-Efficacy Based On Language Online Learning Environment In Higher Education - Rizky Eka Prasetya (Journal of English Language Learning, 2021)
The Learning Management System (LMS) self-efficacy determined that the learner established their capabilities and confidence through a positive mindset of virtual learning activities. The integration of experiences and abilities was developed to impact Moodle as an electronic facility efficiently. The purpose of the study was to aim the investigations and determination to the LMS Moodle Self-efficacy in language learning pedagogy. The study’s design was conducted mixed research method collaborated to the quantitative and qualitative approach, and sequential basic structuralized applied to the sequential phase (quantitative and qualitative). The objective of the study took on the 257 language learners in Higher Education. The application scale of LMS Moodle self-efficacy integrated into language learning in Higher. It involved the 22 questionnaires in selecting dichotomy to agree and disagree point of the Likert scale. The study’s result had exposed the three-scales enhance to the platform of Moodle self-efficacy of accessing, Moodle self-efficacy of communication, and Moodle self-efficacy of electronic testing and feedback. The exploratory LMS Moodle self-efficacy had a maximum point range of around 0.73 and 0.92, and the condition had established to the participants’ respondents and variation in each statement. Consequently, these three scales demonstrated unbiased responses toward the questionnaire items. The online language learners conduced to comprehend Moodle become the adaptive LMS to implement the English language learning strategy completely. Nevertheless, the communication and versatility access needed to develop well in conducting language learning content so learners would feel encouraged and motivated following virtual language learning.